COMMUNITY STRUCTURE OF MACROZOOBENTHOS AS AN INDICATOR QUALITY OF COASTAL WATERS IN TANAH MERAH VILLAGE - Kasmira, Febriyanti; Nasution, Syafruddin; Mubarak, Mubarak (Asian Journal of Aquatic Sciences, 2023)
This research was conducted in January 2022 in the coastal waters of Tanah Merah Village and at the Marine Biology Laboratory and Marine Chemistry Laboratory, Department of Marine Science, University of Riau. The purpose of the study was to analyze the structure of macrozoobenthos communities in the coastal waters of Tanah Merah Village which includes the type, abundance, diversity, uniformity, dominance index, and similarity of communities. As supporting data in this study, several environmental parameters were also measured which included water quality, sediment type, and sedimentary organic matter content. The research method used is the survey method, where sampling using the squared transect method is carried out at 3 stations. Based on the results of the study found 13 species of macrozoobentos. A species that is found at all stations is Nerita articulate. The abundance of macrozoobenthos is 12,300 ind/ha. The diversity index value (H') of 1.42, indicates a moderate category, namely water quality is still maintained, a uniformity index (E) of 1.66, is classified as a high category, namely water quality is still supportive for macrozoobenthos life, the dominance index (C) 0.17, is included in the low category. In the community similarity index between I and II, 25% of types are not the same, inter-station I and III 43% of types are almost the same, and inter-station II and III 16% of types are not the same. Water quality parameters are as follows: temperature 27-29oC; salinity 30-31 ppt; pH 6-7; DO 3.6-7.6 mg /l. Sedimentary organic matter 4.47-23.53%, muddy sediment type. Based on the value of the aquatic quality biological index at the research site, it is still in good condition.